Penghematan Inventory Jenis Consignment-Kanban dengan Meminimumkan K-Max di Plant Y PT X - Jason Averell Lumanto; Herri Christian Palit (Jurnal Titra, 2020)
PT X is a company that works in manufacturing electrical components. One of their plants called Y plant has a mini warehouse that functions as a buffer for inventory between the main warehouse (A plant) and the production line on Y plant. One of the challenges currently present at Y plant’s mini warehouse is the high value of consignment-Kanban inventory maximum Kanban capacity (K-max), reaching up to 200,073 for 445 part numbers. This problem is caused by the imbalances between certain part numbers’ K-max quantity and their actual average daily usage in real life. The proposed solution for this problem is to recalculate their K-min and K-max quantities by using the latest data that represent their real life conditions. The proposed solution is then implemented to 339 out of 445 consignment-Kanban type part numbers. This implementation brings reduction to the total K-max quantity by 43.96% reduction, and reduction to the total K-max value by 43.98%.